2020
DOI: 10.1001/jamasurg.2020.2497
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Low Muscle Mass and Low Muscle Radiodensity With Morbidity and Mortality for Colon Cancer Surgery

Abstract: IMPORTANCE Given the risks of postoperative morbidity and its consequent economic burden and impairment to patients undergoing colon resection, evaluating risk factors associated with complications will allow risk stratification and the targeting of supportive interventions. Evaluation of muscle characteristics is an emerging area for improving preoperative risk stratification.OBJECTIVE To examine the associations of muscle characteristics with postoperative complications, length of hospital stay (LOS), readmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
122
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 59 publications
(111 reference statements)
13
122
2
3
Order By: Relevance
“…Several factors may contribute to the discrepancy. Firstly, the present study noticed that gender has a significant impact on all body composition parameters evaluated, in line with previous reports [ 46 ]. Therefore, the cut-off level of each body composition parameter and the subsequent statistical analysis were gender dependent in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Several factors may contribute to the discrepancy. Firstly, the present study noticed that gender has a significant impact on all body composition parameters evaluated, in line with previous reports [ 46 ]. Therefore, the cut-off level of each body composition parameter and the subsequent statistical analysis were gender dependent in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Several factors may contribute to the discrepancy. Firstly, our study noticed that gender has a signi cant impact on all these body composition parameters, which has been reported before [35]. Therefore, the cut-off of each body composition parameter and the subsequent statistical analysis were gender dependent in our study.…”
Section: Discussionsupporting
confidence: 62%
“…Several studies have evaluated body composition related to post-surgical complications in cancer patients. Recently, Xiao et al showed that both low SMI and low SMD were associated with a higher risk of postsurgical complications, and short-term and long-term mortality in patients with colorectal cancer [ 48 ]. In a similar population of the same nationality, using the same cut-off points for low SMI, Maurício et al [ 42 ] observed that low SMI and low muscle strength were associated with short-term postoperative complications in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…SMD reflects the lipid content of the muscle, and SMI reflects the skeletal muscle volume or mass and it is measured as the skeletal muscle area divided by body height squared [ 51 ]. One possible explanation for this could be that the increase in lipid content of the muscle (myosteatosis) occurs before the decline in the size of muscle mass, and the deterioration of muscle is often occult, particularly in the presence of obesity [ 48 ]. Also, CT-based calculation allows for early detection of reduction in HU (SMD) while the muscle area remains unchanged; thus decrease in SMD is detected earlier than the corresponding decrease in SMI [ 52 ].…”
Section: Discussionmentioning
confidence: 99%